Dual-functionalized nanostructured biointerfaces by click chemistry - Schenk, Franziska C.; Böhm, Heike; Spatz, Joachim P.; Wegner, Seraphine V. (Langmuir, 2014)
The presentation of biologically active molecules at interfaces has made it possible to investigate the responses of cells to individual molecules in their matrix at a given density and spacing. However, more sophisticated methods are needed to create model surfaces that present more than one molecule in a controlled manner in order to mimic at least partially the complexity given in natural environments. Herein, we present dual-functionalized surfaces combining quasi-hexagonally arranged gold nanoparticles with defined spacings and a newly developed PEG-alkyne coating to functionalize the glass in the intermediate space. The PEG-alkyne coating provides an inert background for cell interactions but can be modified orthogonally to the gold nanoparticles with numerous azides, including spectroscopically active molecules, peptides, and biotin at controlled densities by the copper(I)-catalyzed azide alkyne click reaction. The simultaneous presentation of cRGD on the gold nanoparticles with 100 nm spacing and synergy peptide PHSRN in the space between has a striking effect on REF cell adhesion; cells adhere, spread, and form mature focal adhesions on the dual-functionalized surfaces, whereas cells cannot adhere on either monofunctional surface. Combining these orthogonal functionalization methods creates a new platform to study precisely the crosstalk and synergy between different signaling molecules and clustering effects in ligand-receptor interactions.
Gesehen am 10.08.2020